Redefining Prevention and Care: A Status-Neutral Approach to HIV. (2nd May 2018) - Myers, Julie E; Braunstein, Sarah L; Xia, Qiang; Scanlin, Kathleen; Edelstein, Zoe; Harriman, Graham; Tsoi, Benjamin; Andaluz, Adriana; Yu, Estella; Daskalakis, Demetre
Abstract: Recent biomedical advances inspire hope that an end to the epidemic of HIV is in sight. Adopting new approaches and paradigms for treatment and prevention in terms of both messaging and programming is a priority to accelerate progress. Defining the key sequential steps that comprise engagement in HIV care has provided a useful framework for clinical programs and motivated quality improvement initiatives. Recently, the same approach has been applied to use of pre-exposure prophylaxis for HIV prevention. Building on the various prevention and care continua previously proposed, we present a novel schematic that incorporates both people living with HIV and people at risk, making it effectively "status-neutral" in that it proposes the same approach for engagement, regardless of one's HIV status. This multidirectional continuum begins with an HIV test and offers 2 divergent paths depending on the results; these paths end at a common final state. To illustrate how this continuum can be utilized for program planning as well as for monitoring, we provide an example using data for New York City men who have sex with men, a population with high HIV incidence and prevalence.